LIFE CYCLE AND HABITS OF Anticarsia gemmatalis SOY PEST IN THE VALLEY OF CAUCA - DE GUTIÉRREZ, BERTHA; PULIDO-F., JAIME (Revista Colombiana de Entomología, 1978)
The Velvetbean Caterpillar (Anticarsia gemmatalis Hubner) is considered to be the principal insect pest affecting soybean crops in the Cauca Valley (Colombia). Control generally requires two to three applications of insecticides, a factor which increases the production cost of the crop. The present study was designed to obtain information regarding the life cycle, habits, hose plants, and natural enemies of A. gemmatalis. lnvestigations were conducted in the Entomological Laboratory and soybean cultivations of the Colombian Agricultura Institute (ICA) in Palmira, Valle. Experimental temperature and relative humidity averaged 24,15°C and 72,87%, respectively. Egg, larva, prepupa, and pupa stages averaged 3,17; 13,83; 1,46; and 11,04 days in duration, respectively. Six instars were observed in the larval stage with durations (in sequence) of 2,96; 1,35; 1,87; 1,55; 2,22; and 3,88 days. Sexes were separated on the basis of the location of the genital aperture of the pupae. Longevity of adult females and males averaged 16,72 and 12,89 days, respectively. A preoviposition period of 0-2 days was observed. The number of eggs ovisposited per female ranged from 61 to 888 with a mean of 402,38. Maximum oviposition occurred 3-6 days after mating. The principal natural enemies of Anticarsia are Euplectrus n. sp. (ne: comstockii) (Hymenoptera: Euiophidae) and the fungus Nomuraea(=Spicaria) rileyi Farlow. Euplectrus n. sp.v parasit A. gemmatalis in the larval stage, before a significant economic damage in produced. The following plants (family Leguminosae) were observed to be hosts: Phaseolus lathyroides L. (frijol de los arrozales);  P. calcaratus Roxb., (frijolito rojo); Dolichos lablab L. (frijol jacinto); Stizolobium deeringianum Bort (frijol terciopelo) and Medicago sativa L. (alfalta).